2011
DOI: 10.1111/j.1365-2710.2011.01266.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of medication-related problems among patients with renal compromise in an Indian hospital

Abstract: Medication-related problems are frequent in renally compromised patients in our patient population. The high level of acceptance of clinical pharmacist's recommendations by the nephrologists demonstrates that clinical pharmacists may help improve overall patient care in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 24 publications
4
18
1
1
Order By: Relevance
“…Cardiovascular agents and anti-infective agents were the most common therapeutic class of medications implicated with drug related problems. This result is consistent with the studies carried out by Sathvik et al, Krska J et al, Zaher Al Salmi and Al-hajje et al 17,18,19,20 where cardiovascular agents were the highest rate associated with drug related problems but differ from the studies carried out by Struck P et al 21 in which antibiotics are the most frequently involved in drug related problems. The reason for the difference in the therapeutic classes involved may be because of the differences in the underlying diseases.…”
Section: Discussionsupporting
confidence: 90%
“…Cardiovascular agents and anti-infective agents were the most common therapeutic class of medications implicated with drug related problems. This result is consistent with the studies carried out by Sathvik et al, Krska J et al, Zaher Al Salmi and Al-hajje et al 17,18,19,20 where cardiovascular agents were the highest rate associated with drug related problems but differ from the studies carried out by Struck P et al 21 in which antibiotics are the most frequently involved in drug related problems. The reason for the difference in the therapeutic classes involved may be because of the differences in the underlying diseases.…”
Section: Discussionsupporting
confidence: 90%
“…The most common type of DRPs was overdosage (38%), as shown in Table 2. This finding was linier with the finding from a study conducted by Prasanna et al [7] and Castelino et al [8], which confirmed the high dose of prescribing as the major DRPs. Yet, this finding was different with the finding from a study conducted by Samoy et al [9] which confirmed that adverse drug reactions was the most frequent of DRPs.…”
Section: Resultscontrasting
confidence: 45%
“…The types of medications associated with MRPs in our study portrayed the common prescribing pattern in the paediatric population [ 3 , 21 , 22 ]. However, medicines of the “blood and blood forming agents” are unique to MRPs in renal patients [ 12 , 13 , 23 , 24 ]. The medications that were more often associated with MRPs were also those more often prescribed.…”
Section: Discussionmentioning
confidence: 99%